Factors Influencing Antenatal Care Service Utilization among Migrant Women in Bangkok Metropolitan Area - Thitichotrattana , Pailin; Pungbangkadee, Rudee; Ratinthorn, Ameporn (Nursing Science Journal of Thailand, 2024)
Purpose: To investigate the factors that influence antenatal care services utilization among migrant women in the Bangkok metropolitan area. Design: Predictive study design. Methods: The sample was 180 Myanmar migrant women who gave birth at Bhumibol Adulyadej Hospital and Lerdsin Hospital during February - July 2022. The data were collected by using 6 questionnaires including personal and pregnancy data, knowledge about antenatal care, attitude toward antenatal care, social support, health service resources, and risk of pregnancy questionnaires. Data were analyzed by frequency, percentage, mean, standard deviation, chi-square test, and logistic regression analysis. Main findings: The results revealed that the migrant women with good social support were 4.44 times more likely to receive adequate antenatal care services than those with moderate and low social support (AOR = 4.44; 95%CI = 1.25, 15.80; p < .05). The migrant women with social security scheme were 2.94 times more likely to receive adequate antenatal care services than uninsured ones (AOR = 2.94; 95%CI = 1.41, 6.13; p < .05). Significant difference was not found between the group with health insurance card and the uninsured group. Knowledge about antenatal care, attitude toward antenatal care, perceived convenience of visiting health service resources, and risk of pregnancy could not influence adequate antenatal care utilization. Conclusion and recommendations: Only social support and health insurance factors significantly influence adequate antenatal care services utilization. Services should be promoted among migrant pregnant women by informing them about the benefits of having insurance for health. Social support should be assessed during prenatal care so that a necessary support from significant others to receive prenatal care as required would be planned and implemented.